Active control of flexible structures using distributed sensors and actuators - Teo, Boon Kiat. (2008)
Smart structures consist of highly distributed sensors and actuators and controllers are used to coordinate between the sensors and actuators. Many previous studies have shown that distributed control systems exhibit favorable outcomes in suppressing the vibration of structures. In this project, a methodology has been developed to determine the optimal location of distributed actuators and to compute the optimal gains of the controller to suppress the structural vibration. The optimal locations for sensors are also investigated. The present method is based on a finite element method approach, modal reduction, continuous-time linear quadratic regulator (LQR) and continuous-time linear quadratic gaussian (LQG). The computed gains of the controller are then digitized into microprocessor by the bilinear transformation.